2021
DOI: 10.1007/s11606-021-06990-4
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between History of Depression and Access to Care Among Medicare Beneficiaries During the COVID-19 Pandemic

Abstract: Background Depression is associated with a higher risk for experiencing barriers to care, unmet social needs, and poorer economic and mental health outcomes. Objective To determine the impact of COVID-19 on ability to access care, social and economic needs, and mental health among Medicare beneficiaries with and without depression. Design and Participants Cross-sectional study using data from the 2020 Medicare Current Beneficiary Survey COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…These conditions may have limited the type of care and risk of accessing care. Mental health status is also associated with disparities in health care access ( 16 , 23 , 24 ) and may be related to gaps in Medicare coverage for mental health disorders ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions may have limited the type of care and risk of accessing care. Mental health status is also associated with disparities in health care access ( 16 , 23 , 24 ) and may be related to gaps in Medicare coverage for mental health disorders ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Depression has been associated with greater inability to access care, more unmet social needs, and poorer economic and mental health outcomes, suggesting greater risk for adverse health outcomes. 27…”
Section: Always Begin With the Evidencementioning
confidence: 99%
“…Literature has shown that older adults with depression are at greater risk for suicide and increased morbidity and mortality (Balasuriya et al, 2021; Conwell et al, 2011), and vulnerable to the decline in daily functioning, independence, and quality of life (Polacsek et al, 2019). Additionally, late life depression also poses challenges to the caregivers (e.g., stress, financial burden) and the society (e.g., increased healthcare costs) (Pocklington, 2017).…”
Section: Introductionmentioning
confidence: 99%